2017
DOI: 10.1080/10408444.2017.1391170
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cancer hazards of bitumen emissions – a case study for complex petroleum substances

Abstract: When assessing cancer hazard and risk associated with a complex petroleum substance, like bitumen emissions, there are often conflicting results related to human, animal and mechanistic studies. Validation of the complex composition to assure that it matches real-world exposures and control of confounders are pivotal factors in study design to allow the necessary read-across during assessments. Several key studies on bitumen emissions in two-year dermal cancer assays reported variable outcomes ranging from hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 95 publications
0
11
0
1
Order By: Relevance
“…The highly aromatic sulfur-containing compound emissions include formulas representing benzothiophenes and dibenzothiophenes, a selection of which have been previously observed as individual compounds (fig. S6) ( 45 , 46 ). However, previous studies have not reported the wide range of other aromatic and non-aromatic sulfur-containing compounds in asphalt-related emissions.…”
Section: Resultsmentioning
confidence: 99%
“…The highly aromatic sulfur-containing compound emissions include formulas representing benzothiophenes and dibenzothiophenes, a selection of which have been previously observed as individual compounds (fig. S6) ( 45 , 46 ). However, previous studies have not reported the wide range of other aromatic and non-aromatic sulfur-containing compounds in asphalt-related emissions.…”
Section: Resultsmentioning
confidence: 99%
“…The highly aromatic S-containing compounds in bitumen emissions include chemical structures representing benzo-thiophenes and dibenzo-thiophenes . The complex mixture of O-containing emissions includes chemical structures representing benzofurans and dibenzofurans, commonly found in complex petroleum-based mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…These active organic compounds function as precursors to ozone and SOAs. , Asphalt pavement and asphalt binder (bitumen; a petroleum-derived substance) have been identified as a potential missing source of volatile and semivolatile organic compounds that are released into the atmosphere in the form of gas or aerosol . Bitumen emissions include thousands of individual chemical compounds that eventually form particles with varying aerodynamic diameters (from nm to μm) and different toxicological properties that can be a potential hazard for human health and climate. , These emissions are temperature-dependent compounds that are doubled in a temperature rise from 40 to 60 °C; they reach the maximum level at temperatures over 140 °C, indicating that SOA precursors are released into the air more significantly in summer months . Exposure to ultraviolet is also an influential factor accelerating the emission of volatile and semivolatile organic compounds from areas surfaced with bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds of bitumen are polar compounds carrying S-, N-, and O-containing functional groups such as thiol, amine, amide, phenol, carboxyl, and alcohol. In our list of polar compounds selected for interaction with zeolite, some polar compounds such as benzoic acid, benzofuran, hexanethiol, and hexanal are volatile or semi-volatile compounds of bitumen that can be emitted from the bituminous composites, negatively impacting both air quality and the durability of composites. , For many years, asphalt pavement and asphalt binder (bitumen) have been known as sources of hazardous emissions during hot applications . However, recent findings show that asphalt emissions are not limited to high temperatures during the production of asphalt mixtures or paving operations; there are continuous emissions at ambient temperatures, and the emissions significantly worsen when surfaces are exposed to solar radiation or high temperatures …”
Section: Methodsmentioning
confidence: 99%
“…68,69 For many years, asphalt pavement and asphalt binder (bitumen) have been known as sources of hazardous emissions during hot applications. 70 However, recent findings show that asphalt emissions are not limited to high temperatures during the production of asphalt mixtures or paving operations; there are continuous emissions at ambient temperatures, and the emissions significantly worsen when surfaces are exposed to solar radiation or high temperatures. 12 ■ RESULTS AND DISCUSSION Laboratory Experiments.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%